CYBERBULLYING AND MENTAL HEALTH AMONG ADOLESCENTS: THE ROLE OF ATTITUDES - Irina L. Zinovieva; Plamen P. Kalchev (Journal of IMAB)
Purpose: Apart from being an institution, the school is also a human community that functions to a large extent in virtual social networks. Some destructive interactions within the latter have the potential to significantly reduce the school's contribution to student development. The present research aims to examine the extent of cyberbullying among students and the role of attitudes towards cyberbullying in the process of taking cyberaggressive actions. Material/Methods: Bulgarian versions of two questionnaires were used - on cyberbullying and on attitudes towards cyberbullying in a study of 658 students aged between 14 and 18 (M=15.68, SD=1.21). Results: A high degree of cyberbullying was found, and a "spiral of aggression" mechanism has been described, in which the components mutually support and reinforce each other. As a prerequisite for cyberbullying, three main attitudes have been identified - publicity, absence of direct contact and immediate reinforcement of the cyberaggressor's actions, the latter having the greatest contribution to the transition to aggressive online actions. Conclusions: We analyse the relationship between attitude towards cyberbullying and the cyberbullying consequences for mental health in the generative artificial intelligence era. On the basis of the obtained results, actions towards cyberbullying prevention are indicated, focusing on the attitudes.